Efeito de processamentos do suco integral de laranja sobre suas características de qualidade - Souza, Darliane Veras dos Santos (Universidade Federal Rural do Semi-Árido, 2019)
In the orange juice industry, heat treatment is used to neutralize the action of pathogenic microorganisms. However, such action can cause nutritional losses in the juice. In this way, the objective of this work was to evaluate the microbiological safety, the physico-chemical quality and the antioxidant potential of whole juice of 'Lima' orange processed by conventional thermal method and to compare it with the plasma processing. For microbiological evaluation, a completely randomized experiment, with 5 replicates, was conducted. Escherichia coli and Candida albicans were inoculated in the sterile juice, then, the following treatments were applied: atmospheric plasma (14 kV voltage, 400 Hz frequency) in 5 mL juice for 1 min; and heat treatment (87 °C) in 50 mL juice for 1 min; a sample of juice contaminated with microorganism not treated (negative control) and autoclaved juice sample (absolute control). After this process, the infected juice sample with E. coli was plated in culture medium agar VRB (Violet Red Bile) and the juice infected with C. albicans was plated in culture medium BDA (Potatoe dextrose agar), both inoculated under 36º C during 24 h in Biological Demand Oxygen (B.O.D.), for counting of colony forming units. Moreover, to evaluate the physical-chemical and bioactive compounds, a second experiment was conducted in a completely randomized design, in a 3 x 5 factorial scheme (technologies of treatment x days of evaluations), with five replicates. In this experiment, juice samples were neither autoclaved nor inoculated with microorganisms, but, similarly, they were submitted to plasma and heat treatments, and a not treated sample juice was used as control. The juice samples were assessed with respect to: color, pH, titratable acidity (AT), soluble solids (SS), SS / AT ratio, total and reducing sugars, vitamin C, carotenoids, yellow flavonoids, polyphenols and antioxidant activity throughout 16 days, with evaluations each four days. Then, the juice samples were stored during 16 days under 2 ± 1 °C and 53 ± 3% R. H. The application of plasma and heat treatment reduced the amount of the bacterium E. coli in juice, inactivation of 16.72 and 100%, respectively. The plasma did not inactivate C. albicans in whole orange juice. The thermal treatment inactivated 100% C. albicans. The plasma and heat treatment changed the color, with an increase in the values of brightness and hue angle. The application of plasma reduced levels of vitamin C, carotenoids and polyphenols; yellow flavonoids have increased. The juice that passed through heat treatment, soon after the process, reduced the content of carotenoids. However, the heat treatment and the plasma did not have undermine the antioxidant activity
Keywords: C. albicans; Compostos bioativos; Cor; E. coli; Tratamento não-térmico; Bioactive compounds; Candida albicans; Color; Escherichia coli; No-heat treatment; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA